Hydrological coupling between subglacial water conduits, eskers, and ice-shelf channels across the grounding line of an Antarctic ice shelf - Drews, Reinhard; Pattyn, Frank; Hewitt, Ian; Ng, Felix; Berger, Sophie; Matsuoka, Kenichi; Helm, Veit; Nicolas, Bergeot NB; Favier, Lionel; Neckel, Niklas (2017)
info:eu-repo/semantics/published